2022
DOI: 10.3389/fnut.2022.854655
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Preconditioning Alleviated Radiation-Induced Ovarian Dysfunction in Female Mice

Abstract: Radiological therapy/examination is the primary source of artificial radiation exposure in humans. While its application has contributed to major advances in disease diagnosis and treatment, ionizing radiation exposure is associated with ovarian damage. The use of natural products, either alone or as an adjunct, has become increasingly common for reducing the side effects of radiological therapy during disease treatment. Herein, we explored the protective effect of folic acid (FA), a widely used B vitamin, aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Additionally, increased expression of SASP markers in the ovaries led to premature ovarian failure, suggesting that SASP may contribute to ovarian ageing [ 45 ]. Moreover, inhibiting GC proliferation may interfere with proper follicular development and resulted in a decline in ovarian function [ 46 ]. Our findings revealed that miR-143-3p overexpression inhibited GC proliferation and induced SASP factors by targeting UBE2E3.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, increased expression of SASP markers in the ovaries led to premature ovarian failure, suggesting that SASP may contribute to ovarian ageing [ 45 ]. Moreover, inhibiting GC proliferation may interfere with proper follicular development and resulted in a decline in ovarian function [ 46 ]. Our findings revealed that miR-143-3p overexpression inhibited GC proliferation and induced SASP factors by targeting UBE2E3.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether similar protection can be conferred to mitochondrial DNA has yet to be investigated. In our current study, we created a formula containing 10 different ingredients with antioxidant properties, which have been shown to be beneficial against radiation-induced damage by reducing lethality [ 21 ] or attenuating markers of DNA and cellular damage [ 18 , 19 , 20 ], including quercetin [ 22 , 23 ], astaxanthin [ 24 ], zeaxanthin [ 25 ], vitamin C [ 26 ], vitamin B 12 [ 27 ], selenium [ 28 ], folate [ 29 ], CoQ10 [ 30 , 31 ], α-lipoic acid [ 32 ], and vitamin E [ 33 ]. Importantly, we specifically chose to include CoQ10, vitamin E, and α-lipoic acid, as they were the main components of a multi-ingredient supplement that we have shown lowered lactate and oxidative stress markers in patients with primary mitochondrial myopathy [ 34 ].…”
Section: Introductionmentioning
confidence: 99%